EVALUASI MUTU PELAYANAN DAN HUBUNGAN ANTARA KEPUASAN KONSUMEN DAN PELAKSANAAN PELAYANAN KEFARMASIAN OLEH APOTEKER PENGELOLA APOTEK DI APOTEK-APOTEK KOTA KENDARI - Sunandar Ihsan; Putri Rezkya; Nur Illiyyin Akib (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Pharmaceutical service  quality relate to consumer’s  satisfaction.  Twenty five percent   curage  of patient can be  found  from  good  pharmaceutical  sevice  and  75%  from  drug  usage.  This  study  aimed  to  determine pharmaceutical  service  quality  in  community  pharmacy  of  Kendari  City  and  to  determine  correlation  between  consumer’s  satisfaction  and  implementation  of  pharmaceutical  service  by  pharmacist  manager.  This  study  is  an observational analytic. Data collected from 519 respondents  through questionnaires in June-August 2014 spread across  ten  community  pharmacies  City  of  Kendari  with  sampling  method  used  simple  random  sampling,  and accidental  sampling  for  pharmacist  manager.  Correlation  test  used  to  determine  correlation  between  cons umer satisfaction and implementation of pharmaceutical care by pharmacist manager in pharmacy. The result showed that the percentage rate is 76.70% for consumer satisfaction with moderate category. Fixed percentage of any document procedures  and  dispensing  time  is  60%  with  moderate  category.  Pharmacist  manager  percentage  that  manages quality guarantee is 40% with less category.  Statistic correlation test showed that there is no cerrelation between consumer satisfaction and implementation of pharmaceutical care by pharmacist manager in pharmacy with p value 0,268 (> 0,05). Keywords: quality service, pharmaceutical service, consumer satisfaction